Police recruitment and retention for the new millennium : the state of knowledge - Wilson, Jeremy M., 1974- (Rand Corporation monograph series, 2010)
The supply of and demand for qualified police officers are changing in a time of increasing attrition, expanding law-enforcement responsibilities, and decreasing resources. These contribute to the difficulties that many agencies report in creating a workforce that represents community demographics, is committed to providing its employees the opportunity for long-term police careers, and effectively implements community policing. This book summarizes lessons on recruiting and retaining effective workforces.